2009
DOI: 10.1126/science.1179052
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of an Infectious Retrovirus, XMRV, in Blood Cells of Patients with Chronic Fatigue Syndrome

Abstract: Viral Link to Chronic Fatigue Chronic fatigue syndrome (CFS) is a complex and debilitating disorder that is often linked to immune system dysfunction but whose cause(s) remain mysterious. Lombardi et al. (p. 585 , published online 8 October; see the Perspective by Coffin and Stoye ) now present a tantalizing new lead. In blood samples from 101 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
756
25
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(793 citation statements)
references
References 26 publications
3
756
25
9
Order By: Relevance
“…If it can be proven that XMRV infection is indeed widespread and can cause prostate cancer and/or other human diseases (1,21,34,41), it is important to identify effective antivirals against this virus. Toward this end, recent studies have shown that HIV-1 RT inhibitors, such as azidothymidine (AZT) (33,35), zidovudine (ZDV), and tenofovir disoproxil fumarate (TDF), as well as the integrase inhibitor raltegravir (35), can inhibit XMRV replication in cell culture to various extents, suggesting that they can be used either individually or as a combination therapy to treat XMRV infection (33,35).…”
Section: Discussionmentioning
confidence: 99%
“…If it can be proven that XMRV infection is indeed widespread and can cause prostate cancer and/or other human diseases (1,21,34,41), it is important to identify effective antivirals against this virus. Toward this end, recent studies have shown that HIV-1 RT inhibitors, such as azidothymidine (AZT) (33,35), zidovudine (ZDV), and tenofovir disoproxil fumarate (TDF), as well as the integrase inhibitor raltegravir (35), can inhibit XMRV replication in cell culture to various extents, suggesting that they can be used either individually or as a combination therapy to treat XMRV infection (33,35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of XMRV in human pathogenesis is controversial (Switzer et al, 2011). XMRV was also reported to be presence in patients with chronic fatigue syndrome (CFS) (Lombardi et al, 2009). However, the link between XMRV and CFS is unclear, because in other studies it has failed to detect XMRV infection in CFS patients Groom et al, 2010;Switzer et al, 2010;van Kuppeveld et al, 2010;Knox et al, 2011;Satterfield et al, 2011;Shin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In der Mehrzahl der später veröffentlich-ten Studien wurde XMRV jedoch in keiner einzigen Probe nachgewiesen [8,9,10,11,12,13]. Bei Wiederholungsuntersuchungen von zuvor am WPI im Rahmen der initialen Studie [3] positiv getesteten CFS-Patienten konnten in unabhängigen Laboren in keinem einzigen Fall XMRV oder spezifische Antikörper gegen XMRV-Proteine nachgewiesen werden, obwohl nahezu identische, hochsensitive Verfahren verwendet wurden [14,15]. Hiermit stellt sich die Frage, was die Ursache für den beschriebenen Nachweis von XMRV am WPI und an einem kommerziellen Labor sowie in den anderen Studien sein könnte.…”
Section: Ursprüngliche Einschätzung Von Xmrv Als Neues Retrovirus Mitunclassified
“…Heute gilt als gesichert, dass alle XMRV-Sequenzen aus der 22Rv1-Zelllinie stammen. Unter Berücksichtigung der oben angeführ-ten Argumente stellt sich daher die Frage nach der Validität der Untersuchungsergebnisse, die in den Arbeiten über positive XMRV-Diagnosen in Patientenproben beschrieben wurden [3]. …”
Section: Entstehung Von Xmrv In Einer In Mäusen Etablierten Humanen Punclassified